CRISPR Target-based Single-guide RNA (sgRNA) for Diagnostic Testing of Hepatitis B Virus - Christian, Jeanne Elvia; Yuliawuri, Hartiyowidi; Suherman, Edvan Arifsaputra (Molecular and Cellular Biomedical Sciences, 2023)
Background: Indonesia is the second-highest country with hepatitis B cases in the South East Asian region. Clustered regularly interspaced short palindromic repeats (CRISPR)-CRISPR associated protein 12 (Cas12) could be developed as a diagnostic tool to detect hepatitis B infection. This study was aimed to develop a diagnostic method for hepatitis B virus by designing CRISPR target-based single-guide RNA (sgRNA).Materials and method: The preCore/Core-gene sequences of hepatitis B virus were collected from the National Center for Biotechnology Information (NCBI) website. The selected sequence was submitted to Cas Designer and CRISPOR tools to design sgRNA. The resulting sgRNA was cloned in silico into an expression vector using Benchling software.Results: The 23-nucleotide sequence 5'- GTAGTCAGTTATGTCAATGTTAA-3’ had 30% GC content, 68.3 out-of-frame and 76 predicted efficiencies. This sequence had no mismatch based on analysis.Conclusion: This preliminary study will help design a CRISPR-based diagnostic kit for the detection of hepatitis B virus in Indonesia. However, further in vitro and in vivo studies are required to demonstrate its potential and efficiency.Keywords: CRISPR-Cas12b, diagnostic, HBV, sgRNA